The wingmen : the unlikely, unusual, unbreakable friendship between John Glenn and Ted Williams - Lazarus, Adam (Citadel Press, Kensington Publishing Corp., 2023)
"The untold story of the unique fifty-year friendship between two American icons: John Glenn, the unassailable pioneer of space exploration and Ted Williams, indisputably the greatest hitter in baseball history. It was 1953, the Korean War in full throttle, when two men--already experts in their fields--crossed the fabled 38th Parallel into Communist airspace aboard matching Panther jets. John Glenn was an ambitious operations officer with fifty-nine World War II combat missions under his belt. His wingman was Ted Williams, the two-time American League Triple Crown winner who, at the pinnacle of his career, had been inexplicably recalled to active service in the United States Marine Corps. Together, the affable flier and the notoriously tempestuous left fielder soared into North Korea, creating a death-defying bond. Although, over the next half century, their contrasting lives were challenged by exhilarating highs and devastating lows, that bond would endure."--